Evaluation in uniform nurseries - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The CIAT Bean Program uses a 3-stage progeny evaluation program asfollows: (a) the VEF, which in 1984 contained 1004 entries distributed in 10 groups according to seed color and size, growth habit (bush or climbing), and climatic adaptation; (b) the EP, which consisted of 446 entries and 38 controls, distributed in 14 groups according to seed size and color, and growth habit, each group being planted in randomized blocks with 3 replications under high input conditions in CIAT-Palmira and CIAT-Popayan; and (c) the IBYAN, which in 1984 contained a total of 77 bush bean and 31 climbing bean lines. The results of the different trials carried out in this 3-stage progeny evaluation program are tabulated. (CIAT)